2006
DOI: 10.1016/j.inoche.2006.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative coupling of activated alkynes with palladium(0) olefin complexes: Side production of the highly symmetric hexamethyl mellitate species under mild conditions at low alkyne/complex molar ratios

Abstract: The reactions of oxidative coupling of dimethylacetylene dicarboxylate (DMA) with palladium (0) olefin complexes bearing a pyridylthioether as ancillary ligand give rise to the corresponding palladacyclopentadienyl complexes as the main product and in some cases to the highly symmetric hexamethyl mellitate molecule, especially when a low alkyne(DMA)/complex ratio is employed. A plausible mechanism based on several pieces of experimental evidence is proposed, and the most effective complexes promoting the hexam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Treatment of 151 with dimethyl acetylenedicarboxylate, even at room temperature, led to the formation of the aromatic product. Canovese et al 205 Takahashi et al 211 studied the regioselective synthesis of 2322 zirconacyclopentadienes from the oxidative coupling of two 2323 different alkynes with a low-valent zirconocene precursor. 2324 However, due to the low nucleophilicity of the zirconacyclo-2325 pentadiene, a third unsaturation was not able to insert itself in 2326 the Zr−C bond and, therefore, no benzene derivative was 2327 generated.…”
Section: Iridium Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment of 151 with dimethyl acetylenedicarboxylate, even at room temperature, led to the formation of the aromatic product. Canovese et al 205 Takahashi et al 211 studied the regioselective synthesis of 2322 zirconacyclopentadienes from the oxidative coupling of two 2323 different alkynes with a low-valent zirconocene precursor. 2324 However, due to the low nucleophilicity of the zirconacyclo-2325 pentadiene, a third unsaturation was not able to insert itself in 2326 the Zr−C bond and, therefore, no benzene derivative was 2327 generated.…”
Section: Iridium Complexesmentioning
confidence: 99%
“…Canovese et al reported the oxidative coupling of dimethyl acetylenedicarboxylate with palladium(0) olefin complexes bearing a pyridylthioether ancillary ligand. Reaction of the alkyne and the palladium complex gave palladacyclopentadiene complex as the main product together with some amounts of the palladium–alkyne complex and hexamethyl mellitate.…”
Section: [2 + 2 + 2] Cycloaddition Of Three Alkynesmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative palladium(II) catalysis differs from these in that it utilizes molecular oxygen to regenerate the active catalyst in palladium(II) catalyzed coupling reactions. There are two proposed mechanisms for the catalytic cycle [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, type 2 complexes, which are produced by the equilibrium displacement of an alkene by an activated alkyne, represent a peculiar class of substrates that can accumulate as unreactive species, which, depending on their electronic and steric characteristics, react with an additional molecule of the alkyne to give palladacyclopentadiene derivatives or react with the palladacyclopentadiene itself to yield mellitate derivatives . The understanding of the initial equilibria in the formation of palladacycles is also of crucial importance for a better understanding of the intimate mechanism governing the first step of other catalytic cycles, such as the formation of functional dienes from coupling reactions between alkynes, organic halides, and organotin reagents. , …”
Section: Introductionmentioning
confidence: 99%